ANALYSIS OF FREE FATTY ACID ON SOYBEAN OIL USING GAS CHROMATOGRAPHY – MASS SPECTROSCOPY - Deni Pranowo; M Muchalal (Indonesian Journal of Chemistry, 2004)
Research on transesterification of soybean oil with sodium methoxide as the catalyst in methanol has been conducted. Yields of transesterification reaction were analyzed by gas chromatography-mass spectroscopy (GC-MS). GC-MS spectrum showed that mehtyl palmitic, methyl stearic, methyl oleic and methyl linoleic were produced from the reaction. The reaction was done for 90 minutes and gave convertion of 84.53% (b/b).